Biodiversity of Isopoda and Cumacea (Peracarida, Crustacea) from the Marine Protected Area Namuncurá-Burdwood Bank, South-West Atlantic - Doti, Brenda Lía; Chiesa, Ignacio Luis; Roccatagliata, Daniel Carlos (Polar Biology)
Burdwood Bank is a shallow seamount located south of the Malvinas (Falkland) Islands and east of Tierra del Fuego. In 2013, the area down to 200 m depth of this bank was declared the first open-sea (non-coastal) Marine Protected Area (MPA) in Argentina, and named ?Namuncurá? (MPAN-BB). The present study aimed to evaluate the biodiversity of the isopods and cumaceans from the MPAN-BB. The studied material was collected on board the Argentine RV Puerto Deseado during the Campaña Antártica de Verano 2013. Three stations from the MPAN-BB, respectively located in the core, buffer and transition sectors, were sampled. A total of 17,076 specimens were sorted and 70 taxa distributed in 22 families were identified. Thirty-five new records of distribution and eight species most probably new to science are herein reported. Paramunnidae and Diastylidae were the most abundant and diverse families among isopods and cumaceans, respectively. Our records, together with those obtained from the literature, make a total of 55 nominal species so far known from Burdwood Bank. Except for one nominal species, which had been reported from the Puerto Rico Trench and the Argentine Basin, all the remaining species had also been recorded from other localities within the Magellan Region. In contrast, only nine out of the 55 nominal species had also been reported from the Antarctic Peninsula and/or Scotia Arc. This indicates that the isopods and cumaceans from Burdwood Bank are typically Magellanic, and there is little correspondence between this fauna and that from the Antarctic Peninsula and Scotia Arc. Fil: Doti, Brenda Lía. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Biodiversidad y Biología Experimental y Aplicada. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Instituto de Biodiversidad y Biología Experimental y Aplicada; Argentina Fil: Chiesa, Ignacio Luis. Consejo Nacional de Investigaciones Científicas y Técnicas. ...